1987
DOI: 10.2307/2546621
|View full text |Cite
|
Sign up to set email alerts
|

Health Status, Health Problems and Practices among Refugees from the Middle East, Eastern Europe and Southeast Asia

Abstract: Recent refugees from Poland, Romania, Iraq, and Vietnam were extensively interviewed to assess their health, health care utilization, and health services use barriers. 277 recent arrivals from these countries and 63 previously arrived Laotians comprised the 1983-1985 sample from the Detroit metropolitan area. Results from a 195-item bilingual questionnaire indicated good overall health and little evidence of serious physical health symptoms. Dental health was the area of greatest reported need. Prenatal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…For example, a study conducted with 47 Hungarians, Romanians, Czechoslovakians, Poles, and Gypsies (90 per cent of them were refugees) in the USA referred to a refugee counseling service indicated that majority of them had poor to fair English skills, less than half were employed, 26 per cent had a previous mental health problems and/or marital/family problems (Buchwald et al , 1993). In survey research of Eastern European refugees living in the USA, researchers have found depression, major fears, and anxieties; however, this study pre‐dates the large‐scale immigration of the last 20 years (Young et al , 1987). These mental health challenges were also noted in earlier studies among Eastern European refugees and immigrants seeking help for mental health problems, with those likely to be seen in clinical settings being young, often unmarried, frequently unemployed, having low educational attainment and inadequate English skills (Krupinski et al , 1973).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, a study conducted with 47 Hungarians, Romanians, Czechoslovakians, Poles, and Gypsies (90 per cent of them were refugees) in the USA referred to a refugee counseling service indicated that majority of them had poor to fair English skills, less than half were employed, 26 per cent had a previous mental health problems and/or marital/family problems (Buchwald et al , 1993). In survey research of Eastern European refugees living in the USA, researchers have found depression, major fears, and anxieties; however, this study pre‐dates the large‐scale immigration of the last 20 years (Young et al , 1987). These mental health challenges were also noted in earlier studies among Eastern European refugees and immigrants seeking help for mental health problems, with those likely to be seen in clinical settings being young, often unmarried, frequently unemployed, having low educational attainment and inadequate English skills (Krupinski et al , 1973).…”
Section: Introductionmentioning
confidence: 78%
“…However, the services designed specifically for Eastern European groups are extremely limited. Unfortunately, even where culture specific resources exist, many Eastern European groups view mental health or social service utilization as a sign of weakness (Young et al , 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Children of Holocaust survivors also experience the desire to protect their parents, not wanting to burden their parents, feelings of mourning and loss, prevalent feelings of guilt and anxiety, and heightened sensitivity to suffering people. Since previous research has already determined that Asian survivors of war and political violence suffer psychological disturbances and PTSD symptoms (Abueg & Chun, 1996;Mollica et al, 1987;Ng, 2004;Tummala-Narra, 2001, 2007Young et al, 1987), similar secondary trauma effects may be applicable to Asian Americans who are children of survivors. It can thus be hypothesized that these Asian American children may also be suffering similar symptoms to children of Holocaust survivors.…”
Section: Asian American Traumamentioning
confidence: 99%
“…Contemporary research on Asian Americans actually conclude that many Asian Americans have extensive histories of trauma including pre-immigration political and war trauma, childhood sexual and physical abuse, domestic violence, and rape, in addition to trauma experienced from (im)migration and racism (Abueg & Chun, 1996;Midlarsky et al, 2006;Mollica et al, 1987;Ng 2004;Tummala-Narra, 2001;Weingarten, 2004;Young et al, 1987). In fact, most Asian Americans are immigrants and thus may have survived and/or witnessed large-scale pre-U.S. immigration institutionalized forms of violence and abuse experienced in such armed conflicts and violent events such as the Pacific War, Hiroshima/Nagasaki, the Partition of India, the Korean War, the Cultural Revolution, the Laotian Civil War, the Bangladesh Independence War, the Vietnam War, the Cambodian genocide, Tiananmen Square, and in military dictatorships in many Asian countries during the 20 th and 21 st centuries.…”
Section: Asian American Traumamentioning
confidence: 99%
“…Compared with the general population, language-minority subpopulations contain disproportionately high numbers of vulnerable members of our society, including adults and children living in or near poverty, the less educated, and the elderly. Recent studies have demonstrated that individuals with low levels of English proficiency or who are linguistically isolated2 often have greater than usual difficulties gaining access to medical care and other social services than do English speakers (Young et al, 1987;Zahn, 1999;Phua and McNally, 1999). A lack of proficiency in English may contribute to the disparities in health outcomes among some minority groups.…”
Section: Describing the Language-minority Populationmentioning
confidence: 99%